2020
DOI: 10.1097/hjh.0000000000002326
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin–neprilysin inhibition confers renoprotection in rats with diabetes and hypertension by limiting podocyte injury

Abstract: Objectives: Combined angiotensin receptor--neprilysin inhibition (ARNI) reduces glomerulosclerosis better than single angiotensin receptor blockade (ARB) in diabetic, hypertensive rats. The renoprotective mechanism remains unknown, but may depend on superior blood pressure control, improved renal hemodynamics, suppressed renal inflammation or prevention of podocyte loss. Methods: To address this, TGR(mREN2)27 rats (a model of angiotensin II-dependent hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 53 publications
6
24
1
Order By: Relevance
“…In early stages of diabetic nephropathy, Habibi et al [34] showed that LCZ696 was superior to valsartan in reducing proteinuria, renal ultrastructure, and tubular injury in a murine model. Furthermore, a recent study demonstrated that the renoprotection effect of LCZ696 was attributed by limiting podocyte injury [35]. In the present study, we found that LCZ696 and valsartan treatments did not affect the plasma level of creatinine, an indicator of renal injury.…”
Section: Discussionsupporting
confidence: 52%
“…In early stages of diabetic nephropathy, Habibi et al [34] showed that LCZ696 was superior to valsartan in reducing proteinuria, renal ultrastructure, and tubular injury in a murine model. Furthermore, a recent study demonstrated that the renoprotection effect of LCZ696 was attributed by limiting podocyte injury [35]. In the present study, we found that LCZ696 and valsartan treatments did not affect the plasma level of creatinine, an indicator of renal injury.…”
Section: Discussionsupporting
confidence: 52%
“…Considering the beneficial effects of ANP in the kidney and the deleterious effects of the RAS, the use of a combined inhibition that favors the protective actions of ANP and blocks the harmful effects of Ang II represents an interesting approach to evaluate. In this way, the dual inhibition of the angiotensin receptor AT1 and neprilysin (called ARNI) is a novel therapy that combines a neprilysin inhibitor (sacubitril) that enhances the action of ANP, and a selective antagonist of the AT1 receptor (valsartan) that counteracts the increase in Ang II induced by sacubitril while avoiding the incidence of cough and angioedema caused by ACE inhibitors ( Uijl et al, 2020 ). ARNIs are currently indicated for patients with heart failure (HF) with reduced ejection fraction, where they have shown benefits in terms of morbidity and mortality ( McMurray et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another study demonstrated that treatment with ARNI was associated with increased ANP levels and significant protection against kidney damage in SHRSP rats compared to valsartan alone ( Rubattu et al, 2018 ). Other studies that used an experimental model of angiotensin II-dependent hypertensive diabetic rats [TGR (mREN2) 27 rats] demonstrated that chronic treatment with sacubitril/valsartan was associated with increased in urinary ANP levels, reduced albuminuria, and less development of segmental glomerulosclerosis compared to valsartan monotherapy ( Roksnoer, 2016 ; Uijl et al, 2020 ). This renoprotective effect of ANP would be independent of its antihypertensive efficacy and could be related to a reduction in renal inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…As cardiac function improved, renal perfusion enhanced, followed by an increased GFR. In addition, compared with traditional RASI, ARNI significantly reduced proteinuria, improved renal ultrastructure, and decreased biomarkers of the renal tubulointerstitial lesion ( 30 , 31 ), which is independent of blood pressure reduction. The acting mechanisms are considered as inhibition of inflammation and oxidative stress, as well as drug-specific protection of podocyte integrity ( 30 32 ).…”
Section: Discussionmentioning
confidence: 89%